2018
DOI: 10.1039/c8se00122g
|View full text |Cite
|
Sign up to set email alerts
|

Towards smart free form-factor 3D printable batteries

Abstract: Continuous novelty as the basis for creative advance in rapidly developing different form-factor microelectronic devices requires seamless integrability of batteries. Thus, in the past decade, along with developments in battery materials, the focus has been shifting more and more towards innovative fabrication processes, unconventional configurations, and designs with multi-functional components.We present here, for the first time, a novel concept and feasibility study of a 3D-microbattery printed by fused-fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 25 publications
1
78
0
Order By: Relevance
“…Solidification of each layer is principally based on crystallization and chain entanglement of the polymer, however, addition of additive materials can affect the properties and solidification process of the matrix polymer. Common additives used in polymer matrix for EESDs are various conductive materials like ABS/graphene [26], ABS/carbon [27], PLA/graphene [28] and even PLA/LTO/carbon and PLA/LFP/carbon [29]* which are essential for electrode fabrication in lithium ion batteries. A good example is a recent study [30]** where three conductive agents (Super-P, MWCNTs, graphene) and two active materials (Lithium titanate, lithium manganese oxide) were blended with PLA to test the printability, conductivity and charge storage capacity of the new composite.…”
Section: Materials and Methods Considerationmentioning
confidence: 99%
“…Solidification of each layer is principally based on crystallization and chain entanglement of the polymer, however, addition of additive materials can affect the properties and solidification process of the matrix polymer. Common additives used in polymer matrix for EESDs are various conductive materials like ABS/graphene [26], ABS/carbon [27], PLA/graphene [28] and even PLA/LTO/carbon and PLA/LFP/carbon [29]* which are essential for electrode fabrication in lithium ion batteries. A good example is a recent study [30]** where three conductive agents (Super-P, MWCNTs, graphene) and two active materials (Lithium titanate, lithium manganese oxide) were blended with PLA to test the printability, conductivity and charge storage capacity of the new composite.…”
Section: Materials and Methods Considerationmentioning
confidence: 99%
“…[83] Most frequently used anode active materials in 3D printed Li-ion batteries are graphite, graphene, and lithium titanate (Li 4 Ti 5 O 12 , LTO). [46,52,64,70,108,109] Polymer binders and matrices used for preparation of printable compositions can be thermoplastic polymers (e.g., PLA and ABS), functionalized cellulose, PVDF or aqueous GO. [64,70,108,110] A representative work describing the preparation of highly loaded (up to 62.5 wt%) graphite-PLA conductive composites used as filaments for FDM 3D printing of Li-ion battery negative electrodes was published by Maurel et al [70] Such a high graphite content naturally caused brittleness of produced samples and required the addition of plasticizers (at least 20 wt% and less than 60 wt%) in order to be printable by FDM method.…”
Section: D Printed Active Materialsmentioning
confidence: 99%
“…As in the case of anode materials, polymer binders and conductive additives can also be included in the printable composition to achieve the required conductivity, mechanical and rheological properties of the cathode material. [46,52,[108][109][110][111] Most of the considerations previously discussed for 3D printing of metal oxides and LIB anode materials are also true for LIB cathode materials. The difference between theoretical capacity of active materials and the obtained values along with the poor C-rate performance, commonly reported in connection with polymer-based composites and material extrusion 3D printing techniques, can be explained by insufficient electronic and ionic conductivity of the printed materials due to complete isolation of some amount of conductive materials within polymer matrix.…”
Section: D Printed Active Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li 4 Ti 5 O 12 and LiFePO 4 are the most commonly used anode and cathode materials in 3D‐printed batteries, exhibiting a minimal volumetric expansion, high rate capability, high stability, and security. In recent years, an increasing number of studies on the 3D printing of LTO/LFP‐based electrodes have been reported . The first 3D‐interdigitated microbattery architectures (3D‐IMA) with LTO/LFP materials were developed by the Lewis Group .…”
Section: Electrode Materials For 3d‐printed Batteriesmentioning
confidence: 99%